ANTICANCER AND FREE RADICAL SCAVENGING POTENTIAL OF THE MARINE ALGICOLOUS ENDOPHYTIC FUNGUS CLADOSPORIUM UREDINICOLA - THIRUMALANADHUNI, VASAVI; YERRAGURAVAGARI, LAVANYA LATHA; MATHAKALA, VANI; PALEMPALLI, UMA MAHESWARI DEVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective was to study the antioxidant and anticancer potential of the endophytic fungus Cladosporium uredinicola, isolated from the marine brown alga Dictyota dichotoma. Methods: Anticancer effect of the endophytic fungal extract was evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay using MDA-MB-231 human mammary adenocarcinoma cells as in vitro cancer models. 3T3-L1 pancreatic adipocytes were used as in vitro models for the evaluation of cytotoxic activity against normal cells using MTT assay. Free radical scavenging activity was assessed by 2, 2-diphenyl-1- picrylhydrazyl (DPPH) assay. Results: The ethyl acetate extract of the endophytic fungus showed potent cytotoxic activity against MDA-MB-231 human breast adenocarcinoma cell lines with an inhibitory concentration (IC50) value of 373 μg/ml and a very mild cytotoxic effect on 3T3-L1 Cells with an IC50 value of 2403 μg/ml. DPPH free radical scavenging assay of the extract showed an IC50 value of 359 μg/ml indicating its potential free radical scavenging activity. Conclusion: The results indicated that the endophytic fungus C. uredinicola, isolated from the marine brown alga D. dichotoma, acts as a potential source for anticancer and antioxidant metabolites. Moreover, these anticancer metabolites were observed to be less toxic to the normal cells, which make them prospective therapeutic agents.